THE EFFECT OF WORK DISCIPLINE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT AXIA MULTI SARANA KOTA JAKARTA SELATAN - Yenni Arnas; Susbiyantoro Susbiyantoro; Yhonanda Harsono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The purpose of this study is to determine the Influence between Work Discipline and Work Environment on Employee Performance at PT. Axia Multi Sarana Kota South Jakarta both partially and simultaneously. The research method uses quantitative research methods with a descriptive approach. The sample used in this study was a saturated sample, which used the entire population of 50 people as a sample. ata analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results showed that there was a positive influence between work discipline and partially employee performance. t-test of 4.193 > ttable of 1.677 then Ha1 is accepted and Ho1 is rejected. The results showed that there was a positive influence between the work environment and employee performance partially. t test of 8.179 > ttable 1.677 then Ha2 is accepted and Ho2 is rejected. The results showed that there was a positive influence between the variables of work discipline and work environment on employee performance simultaneously, where the multiple regression equation Y = 10.424 + 0.075 X1 + 0.683 X2 means a positive effect, The multiple correlation test r = 0.767 belongs to the very strong category, the coefficient of determination is 58.8% and the rest is 41.2% which is influenced by other factors, the F test of F is calculated 33.601 > the ftable 3.195 means that it can be concluded that the variables of work discipline and work environment have a significant effect on employee performance.